PRODUCTION OF COCONUT OIIL DIRECTLY FROM FRESH COCONUT MEAT USING THE WASTE HEAT RECOVERY TECHNOLOGY: A "NEW OIL PROCESS" - G. R. Breag; P. Drew; P. G. Joseph (International Coconut Community Journal, 1991)
In several, areas, in Sri Lanka the use of pits for making coconut shell charcoal is restricted or not permitted due to environmental damage or the proximity of human habitation. In addition approximately 50% of the gross heat content of the shells is lost to the surroundings during the process. In view of the above, the Natural Resources Institute developed a coconut shell carbonization unit with waste heat recovery, which virtually eliminates the smoke problem and simultaneously enables the heat generated during the process‑heat normally lost to the surroundings to be used as process heat in the coconut industry. This technology has been commercialized in Sri Lanka and details of the standard capacity (1.5 tonnes shell) unit and its performance are provided. The findings of preliminary trials carried out on the application of the waste heat recovery technology in the production of coconut oil from freshly decorticated macerated coconut meat ‑ bypassing copra production‑are also discussed. The technical and financial aspects of the application of the technology for coconut oil manufacture using the "new oil process" in Sri Lanka are briefly covered and consideration for its adoption in other coconut growing countries is recommended.